2015
DOI: 10.1161/circheartfailure.114.002169
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Myocardial Oxygen Deprivation in Nonischemic Heart Failure

Abstract: Background—Whether the myocardium in nonischemic heart failure experiences oxygen limitation remains a long-standing controversy. We addressed this question in patients with dilated cardiomyopathy (DCM) using a dual approach. First, we tested the changes in myocardial oxygenation between rest and stress states, using oxygenation-sensitive cardiovascular magnetic resonance. Second, we sought to assess the functional consequences of oxygen limitation at rest by measuring myocardial energetics before and after sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
0
23
1
Order By: Relevance
“…They also showed peak systolic myocardial velocity (S′) was a strong correlate of VO 2 . Contributing factors of arterial hypoxemia, low hemoglobin levels, and altered peripheral muscle bioenergetics may also play a role in CO in HF, recent studies, however, have suggested no evidence of myocardial oxygen deprivation in nonischemic HF . We were also unable to demonstrate significant oxygen deprivation during exercise as measured by peripheral oxygen saturation.…”
Section: Discussioncontrasting
confidence: 75%
“…They also showed peak systolic myocardial velocity (S′) was a strong correlate of VO 2 . Contributing factors of arterial hypoxemia, low hemoglobin levels, and altered peripheral muscle bioenergetics may also play a role in CO in HF, recent studies, however, have suggested no evidence of myocardial oxygen deprivation in nonischemic HF . We were also unable to demonstrate significant oxygen deprivation during exercise as measured by peripheral oxygen saturation.…”
Section: Discussioncontrasting
confidence: 75%
“…The failing heart itself is energy-starved (57) and characterized by a down-regulation of FAO (1, 57), which may improve the efficiency of O 2 utilization. It was shown, however, that oxygenation was not impaired in the nonischemic failing myocardium (58), and thus therapeutic strategies that enhance oxidative metabolism, including perhaps NO 3 − supplementation, may be of benefit to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygenation‐sensitive CMR, MPRI and MR Spectroscopy were applied by the same group in patients with dilated cardiomyopathy (DCM) . Interestingly, the presence of impaired myocardial blood flow was not linked to myocardial de‐oxygenation in this population.…”
Section: Utility Of Os‐cmr In Non‐ischaemic Cardiomyopathymentioning
confidence: 99%